Pendampingan dan Penguatan Usaha Mikro Kecil Menengah Melalui Branding dan Digitalisasi Marketing - Ika Devi Perwitasari; Jodi Hendrawan; Fernando Sitepu; Wildanur Anggraini (Forum Kerjasama Pendidikan Tinggi, 2024)
Community service plays an important role in encouraging the development of Micro, Small, and Medium Enterprises (MSMEs), which are the backbone of the national economy. Amidst the challenges of globalization and digitalization, many MSMEs face difficulties in competing, especially in terms of developing branding and utilizing digital technology for marketing. This condition is also experienced by MSMEs in Pekan Kuala Village, which still lack awareness and skills related to effective branding and the implementation of digital marketing strategies. Therefore, mentoring and strengthening MSMEs through branding and digital marketing approaches are important to increase business competitiveness and expand market access. The purpose of this community service program is to strengthen the capacity of MSMEs in Pekan Kuala Village through direct coaching in building brand identity (branding) and utilizing digital media in marketing strategies. Community service partners consist of local MSMEs operating in various sectors, with a focus on businesses that have the potential to develop through strengthening aspects of branding and digital marketing. The implementation methods used in this community service include counseling, training, and intensive mentoring. This activity begins with an analysis of the needs of MSME partners, followed by training on basic branding concepts and digital marketing techniques using platforms such as social media and online marketplaces. In addition, assistance is also provided in the preparation of creative content and targeted digital marketing strategies. Interim results show an increase in participants' understanding of the importance of branding and digitalization, with 85% of MSMEs successfully creating logos and simple marketing content. In addition, around 70% of the assisted MSMEs have actively used social media for promotion. Thus, this assistance program contributes to increasing the competitiveness of MSMEs in the digital era.